Energy storage performance of SrSc0.5Nb0.5O3 modified (Bi, Na)TiO3‐based ceramic under low electric fields. Issue 4 (13th December 2022) - Dai, Zhonghua; Wang, Shengbin; Liu, Yong; Zhang, Fanbo; Liu, Weiguo; Zhao, Xin; Ding, Xiangdong; Fang, Minxia; Ren, Xiaobing
Abstract: Dielectric ceramics with a high recoverable energy density ( W rec ) and high efficiency are desirable for the development of pulsed power capacitors under low electric fields. In this study, through the introduction of SrSc0.5 Nb0.5 O3 into (Bi0.5 Na0.5 Ti0.95 Al0.025 Nb0.025 O3 ) [(1‐ x )BNTA‐ x SSN], a considerable recoverable energy storage density ( Wrec ) of approximately 2.7 J/cm 3 and energy storage efficiency ( η ) of approximately 76 % at 210 kV/cm are achieved at x = .1; additionally, η is further improved to 85 % at x = .2. Moreover, η and W rec of .9BNTA‐.1SSN exhibit outstanding stability (thermal and frequency stability) at 150 kV/cm, which is superior to that of other lead‐free ceramics. The excellent energy storage performance is attributed to the increased relaxation degree and the formation of ferroelectric nanodomains, whereas the enhanced E b is ascribed to the increased electrical resistivity and decreased grain size upon modification. These results indicate the potential of (1‐ x )BNTA‐ x SSN as an ideal candidate for energy‐storage applications.